2017
DOI: 10.3847/1538-4357/aa9983
|View full text |Cite
|
Sign up to set email alerts
|

A Sun-to-Earth Analysis of Magnetic Helicity of the 2013 March 17–18 Interplanetary Coronal Mass Ejection

Abstract: We compare the magnetic helicity in the 17-18 March 2013 interplanetary coronal mass ejection (ICME) flux-rope at 1 AU and in its solar counterpart. The progenitor coronal mass ejection (CME) erupted on 15 March 2013 from NOAA active region 11692 and associated with an M1.1 flare. We derive the source region reconnection flux using post-eruption arcade (PEA) method (Gopalswamy et al. 2017a) that uses the photospheric magnetogram and the area under the PEA. The geometrical properties of the near-Sun flux rope i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 56 publications
(54 reference statements)
3
11
0
Order By: Relevance
“…The large spread in the recovered ϕ r values from single-event analyses reflects the different areas covered by the signatures considered (ribbons, dimmings, and PEAs), and we note that large uncertainties affect the estimation of ϕ r , i.e. up to ±50% of the measured value, as reported by various studies (Qiu et al 2007;Temmer et al 2017;Tschernitz et al 2018;Dissauer et al 2018a;Gopalswamy et al 2017;Pal et al 2017). Despite the scatter, the different values recovered can therefore be considered to be consistent within the (large) error bars.…”
Section: Reconnected Magnetic Fluxessupporting
confidence: 65%
“…The large spread in the recovered ϕ r values from single-event analyses reflects the different areas covered by the signatures considered (ribbons, dimmings, and PEAs), and we note that large uncertainties affect the estimation of ϕ r , i.e. up to ±50% of the measured value, as reported by various studies (Qiu et al 2007;Temmer et al 2017;Tschernitz et al 2018;Dissauer et al 2018a;Gopalswamy et al 2017;Pal et al 2017). Despite the scatter, the different values recovered can therefore be considered to be consistent within the (large) error bars.…”
Section: Reconnected Magnetic Fluxessupporting
confidence: 65%
“…It is defined by R 0 = h/(1 + (1/κ) estimated using equation (1) of Thernisien et al (2006). L is the length of CME flux rope approximated as L = Pal et al 2017), where h leg is the height of the CME flux rope legs (see equation (3) of Thernisien et al (2006)) and (π/2 + α) is in radian. B 0 is the axial magnetic field strength of the CME defined by B cme = φ p x 01 /LR 0 (assuming a force-free CME flux rope).…”
Section: Relative Magnetic Helicitymentioning
confidence: 99%
“…In a force-free magnetic field configuration like a flux rope, the total magnetic helicity is conserved (Woltjer, 1958). Previous studies have suggested that the helicity sign, the total helicity, and the total magnetic flux of an ICME flux rope are related to those of its corresponding source region (e.g., Cho et al, 2013;Hu et al, 2014;Leamon et al, 2004;Möstl et al, 2009;Pal et al, 2017;Qiu et al, 2007). Hence, the property of magnetic helicity conservation can be used to assume that once the flux rope type at the Sun is determined, its chirality is maintained as the CME propagates from the Sun to Earth.…”
Section: Introductionmentioning
confidence: 99%